Sex-specific associations between maternal pregnancy-specific anxiety and newborn amygdalar volumes-preliminary findings from the FinnBrain Birth Cohort Study - Lehtola Satu J.; Tuulari Jetro J.; Karlsson Linnea; Lewis John D.; Fonov Vladimir S.; Collins Louis; Parkkola Riitta; Saunavaara Jani; Hashempour Niloofar; Pelto Juho; Lähdesmäki Tuire; Scheinin Noora M.; et al. (Taylor & Francis, 2022)
Previous literature links maternal pregnancy-specific anxiety (PSA) with later difficulties in child emotional and social cognition as well as memory, functions closely related to the amygdala and the hippocampus. Some evidence also suggests that PSA affects child amygdalar volumes in a sex-dependent way. However, no studies investigating the associations between PSA and newborn amygdalar and hippocampal volumes have been reported. We investigated the associations between PSA and newborn amygdalar and hippocampal volumes and whether associations are sex-specific in 122 healthy newborns (68 males/54 females) scanned at 2-5 weeks postpartum. PSA was measured at gestational week 24 with the Pregnancy-Related Anxiety Questionnaire Revised 2 (PRAQ-R2). The associations were analyzed with linear regression controlling for confounding variables. PSA was associated positively with left amygdalar volume in girls, but no significant main effect was found in the whole group or in boys. No significant main or sex-specific effect was found for hippocampal volumes. Although this was an exploratory study, the findings suggest a sexually dimorphic association of mid-pregnancy PSA with newborn amygdalar volumes.